PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT SIGMA CIPTA CARAKA DI BSD KOTA TANGERANG SELATAN - Erna, Erna; Yunanti, Siska (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of leadership and work discipline on employee performance at PT Sigma Cipta Caraka in BSD, South Tangerang City. The method used is quantitative. The sampling technique used the Slovin formula and a sample of 84 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that leadership has a significant effect on employee performance with a coefficient of determination value of 38.9% and the hypothesis test obtained t count > t table or (7.226 > 1.989). Work discipline has a significant effect on employee performance with a coefficient of determination value of 57.4% and hypothesis testing obtained t count > t table or (10.506 > 1.989). Leadership and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 6.388 + 0.217X1 + 0.581X2. The coefficient of determination value is 63.7% while the remaining 36.3% is influenced by other factors. Hypothesis testing obtained calculated F value > F table or (71.195 > 2.720).